Perioperative POCUS: Technical Considerations and Applications for the Pediatric Anesthesiologist - Allison Heizelman; Rebecca Evans; Emmeline Chuu; Ying Eva Lu-Boettcher (Journal of Clinical Medicine, 2026)
Background: Point-of-care ultrasound (POCUS) use continues to expand across specialties caring for pediatric patients in the perioperative period, offering noninvasive, diagnostic information that complements clinical assessment in real time. Although many POCUS applications were developed and validated in adults, pediatric POCUS requires unique considerations. This review examines the current evidence of diagnostic POCUS within pediatric perioperative care. Methods: A structured search of PubMed was performed for literature published through December 2025, using terms related to point-of-care ultrasound, perioperative care, cardiac, lung, gastric, and airway ultrasound, as well as focused assessment with sonography in trauma (FAST). Priority was given to systematic reviews, meta-analyses, randomized controlled trials, clinical practice guidelines, and landmark observational studies, while supplemented by recent high-quality publications. Findings: POCUS in each of the following areas is discussed: cardiac, pulmonary, airway, gastric, and FAST. Topics for each of the areas include a general overview, considerations for devices and probe selection to optimize imaging, specific uses and applications of the imaging, and potential limitations. Conclusions: POCUS is a valuable tool to complement comprehensive clinical evaluation of children in the perioperative period. Widespread adoption will require additional pediatric normative data, standardized protocols, and structured training for providers. Future research should continue to validate POCUS algorithms and clarify the role of artificial intelligence in enhancing image interpretation and accessibility.